ASSESSMENT OF TORSIONAL IRREGULARITY PROVISIONS FOR BUILDINGS IN ACCORDANCE WITH EUROCODE 8 - Mrdak, Ivan; Rakocevic, Marina; Lađinović, Đorđe (Journal of Applied Engineering Science, 2024)
Irregular structures present a particular design challenge for structural engineers, especially if they are located in seismically active areas. It has been observed that in earthquake-affected areas, structures with a configuration classified as torsionally irregular are more prone to damage than regular structures. Modern seismic provisions have introduced criteria for determining if the structure is torsionally sensitive and guidelines for designing them. Eurocode 8 introduces analitical criterion for checking torsional irregularity with the measures such as torsional ratio and the radius of gyration. If structure is classified as torsionally sensitive, it implies limited structural nonlinear behavior, so the design code prescribes use of reduced behaviour factor, use of 3D model and at least modal analysis as structural investigation method. In order to asses provisions given in Eurocode 8 total 18 structures with different layouts and number of floors were analysed and results presented in this paper. Six layouts of structure were created by varying the position of structural elements in order to create different levels of torsional irregularity. Also, number of stories was varied and structures with 6, 9 and 12 were analysed. Effects of static as well as of accidental eccentricity were considered. The obtained results have shown that with only one level of criteria for torsional irregularity given in Eurocode 8, structures with similar configuration can be classified as torsionally regular of irregular. By classifying structure as torsionally sensitive and applying reduced behaviour factor, significant increase of strength capacity is equally imposed on all elements not only elements that are close to perimeter of structure.